Decompression and Dynamic Transpedicular Stabilization Using Polyetheretherketone Rods and Pedicle Screws vs. Decompression Alone for Single-Level Spinal Canal Stenosis with Listhesis: A Retrospective Case-Control Study - Tosic, Lazar; Baschera, Dominik; Oberle, Joachim; Alex, Alfieri (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Spinal stenosis is frequently caused by spondylolisthesis, and surgical treatment may be indicated. However, whether decompression alone or decompression with dynamic stabilization offers better surgical outcomes remains unclear. We compared the clinical and radiologic results of patients with single-level lumbar spinal stenosis and grade 1 spondylolisthesis undergoing microsurgical decompression alone or decompression with transpedicular dorsal dynamic stabilization.Methods We retrospectively analyzed 20 patients undergoing microsurgical decompression and dorsal dynamic transpedicular stabilization using polyetheretherketone (PEEK) rods in one center from 2011 to 2017. Twenty patients with the same diagnosis undergoing microsurgical decompression alone were used as controls. Reoperation of the index and neighboring segments, back/leg pain, neurologic deficits, and the use of pain medication were assessed. For stabilization patients, radiographic progression of degeneration in the neighboring segments, listhesis degree in the index segment, and implant failure were assessed.Results All patients had good clinical outcomes at 3 and 12 months postoperatively. In stabilization patients, the visual analog scale (VAS) score for leg pain decreased from 5 points (median) to 1.6 at 3 months and 0.6 at 1 year postoperatively. In controls, the VAS score improved from 4.8 points to 1.1 at 3 months and 0.3 at 1 year postoperatively. The VAS score for back pain in stabilization patients decreased from 7.6 points (median) to 1.7 at 3 months and 0.1 at 1 year postoperatively. In controls, it decreased from 7.7 points to 1.1 at 3 months and 0.2 at 1 year postoperatively. In patients with additional dynamic stabilization, a longer hospital stay (stabilization group: 8.7 ± 4.1; control: 6.2 ± 1.6 days), longer operative time (stabilization group: 132.7 ± 41.3; control: 83.2 ± 31.7 minutes), and higher complication rates (revision surgery performed in two stabilization patients) were found.Conclusion No indications in our study showed that additional dynamic stabilization with PEEK rods offers any advantage over decompression alone.
Keywords: polyetheretherketone rod; decompression; spondylolisthesis; back pain; leg pain; stabilization